ESEARCH OF PSYCHOLOGY AND PEDAGOGICAL CONDITIONS OF FAMILY SELF-DETERMINATION OF STUDENT’S YOUTH - Muts, Christina Alekseevna (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2016)
Purpose. Article is devoted to a research of psychology and pedagogical conditions of family self-determination at student’s youth, and also an efficiency evaluation of the program of psikholo-pedagogical maintenance of process of family self-determination of student’s youth. Method and methodology of carrying out work. For an efficiency evaluation of the program of psikholo-pedagogical maintenance of process of family self-determination of student’s youth, we used the method of semantic differential developed by Ch. Osgood, a questionnaire “The level of a ratio of “value” and “availability” in various vital spheres” E. B. Fantalova, a projective technique “Incomplete offers”, “The test the smyslozhiznennykh of orientations” D.A. Leontyeva. In work the mathematico-statistical methods of data processing including calculation descriptive the statistician, Shapiro-Wilks’s criterion, Styyudent’s criterion for dependent selections, nonparametric criterion of Vilkokson were used. Results. Results of work are that having analysed all results of diagnostics it is possible to draw a conclusion that after carrying out the program of psychology and pedagogical maintenance of process of family self-determination of student’s youth, indicators of students increased in such components as values of the matrimonial relations (a parent family, love value, the relation to own family, the attitude towards future marriage partner, the attitude towards themselves, the attitude towards future children, the rights and obligations of spouses), components of an image of the Ya-family man (obraz-Ya, I am future husband / future wife, I am future father / future mother, I am an owner/hostess, I am a son/daughter), marriage motive achievement of success, ideas of temporary prospect (my past, my present). Scope of results. Results can be applied in the subsequent researches on this subject, be used when lecturing on disciplines “Psychology of a family and family consultation”, “Age psychology”, “Psychology of family self-determination”.